PENINGKATAN KESEHATAN HOLISTIK MELALUI EDUKASI PEMBUATAN SIROP HERBAL “SiHebat” KEPADA MASYARAKAT - Fadel, Muhammad Nurul; Besan, Emma Jayanti; Rosnarita, Intan Adevia; Yuliasari, Aulia Wahyu; Besan, Ulfa Nabila (Jurnal Abdi Insani, 2025)
The diversity of herbal plants around us is a potential that has not been optimally utilized. The Nasyiatul Aisyiyah Branch Leadership for the 2024 period requires socialization and education related to health as part of filling the routine monthly religious study activities. This community service program aims to provide education to the Nasyiatul Aisyiyah group in Getas Pejaten, Kudus Regency, regarding the production process and utilization of "SiHebat" herbal syrup based on local plants such as ginger, turmeric, temulawak, and lemongrass, which have various health benefits. Educational activities are carried out through the delivery of material using power point presentation media, with a participatory method that includes a pre-test, material presentation, presentation of herbal syrup making material, and a post-test. The results of the activity showed a significant increase in participants' understanding of the use of herbal plants for health, as indicated by an increase in the average post-test score compared to the pre-test. In addition to providing education, this program also aims to encourage community independence in utilizing local natural resources and opening up business opportunities based on herbal products, in addition it can be used by the community as a reference for developing a product that can increase independence, especially in entrepreneurship. The success of the program is measured through the enthusiasm of the participants, increased knowledge, and the ability to instill the making of herbal syrup, from the results of the Pre-test and Post-test, an increase in community knowledge was obtained in understanding starting from raw materials, efficacy and how to make and rules for using efficacious herbal syrup. From the results of community service in making efficacious herbal syrup, it can provide information and benefits to the community in developing innovations in making herbal preparations, especially in making herbal syrup and in the future this program can be further developed through product diversification and joint research to optimize the benefits of herbal plants for public health.